Common Multiple Primary Cancers Associated With Breast and Gynecologic Cancers and Their Risk Factors, Pathogenesis, Treatment and Prognosis: A Review - Ge, Shuwen; Wang, Bo; Wang, Zihao; He, Junjian; Ma, Xiaoxin (Frontiers in Oncology, 2022)
The mammary gland is closely related to the female reproductive system in many aspects, affecting the whole gynecological system. Breast cancer (BC) is the most common malignancy in women and associated with considerable negative effects. Due to various factors including co-pathogenic genetic mutations, environment factors, lifestyle, behavioral factors, treatment regimens and in-creased survival of patients with BC, there is an increased probability of developing additional primary gynecologic cancers such as ovarian cancer (OC), endometrial cancer (EC), and cervical cancer (CC). More and more studies have been conducted in recent years. Multiple primary cancers (MPCs), also known as multiple primary malignancies, refers to two or more different primary cancers in the same patient occurring in the same or different organs or tissues. The pathogenesis of multiple primary cancers is complex and has a negative effect on the prognosis and survival of patients. This review discusses the common types of BC-associated MPCs, namely, BC associated with OC, BC associated with EC and BC associated with CC, as well as risk factors,pathogenesis, treatment, and prognosis of MPCs associated with breast and gynecologic cancers. It provides new intervention and treatment ideas for patients with BC-associated MPCs to improve quality of life and prognosis.